Land-use regulations and property values in Portland, Oregon: A regression discontinuity design approach - Grout, Cyrus A.; Jaeger, William K.; Plantinga, Andrew J. (Regional science and urban economics, 2011)
Over the past two decades, the tension between public and private interests in the use of land has given rise to state-level legislation seeking to limit government controls on private property. In 2004, voters in Oregon approved Measure 37, which required payments to private landowners for reductions in the value of their property resulting from land-use regulations. The central economic question behind Measure 37 and compensation statutes adopted in other states is, what is the effect of land-use regulations on property values? Economists investigating this question have typically estimated hedonic property value models with regulations included as exogenous regressors. This approach is likely to be invalid if the parcel characteristics that determine property values also influence the government's decision about how to implement regulations. We use Regression Discontinuity Design (RDD) to study the effect of the Portland, Oregon, Urban Growth Boundary (UGB) on property values. RDD provides an unbiased estimate of the treatment effect under relatively mild conditions and is well-suited to our application because the UGB defines a sharp treatment threshold. We find a price differential on the western and southern sides of the Portland metropolitan area ranging from $30,000 to at least $140,000, but no price differential on the eastern side. Support for Measure 37 was fueled by price differences such as these among parcels subject to different regulations, but one must be careful not to view current price differentials as evidence that regulations have reduced property values.